P239 Don't ask, don't tell: Introduction of routine domestic abuse prompt in genitourinary walk-in clinic. (30th June 2016) - Williamson, Marie; Beanland, Frances; Mauger, Andrea; Sacks, Rachel; Mears, Alison
Abstract : Background/introduction: Domestic abuse (DA) is common and spontaneous disclosure rare. In July 2015, routine DA enquiry was introduced in a busy, inner London, walk-in genitourinary medicine clinic. All DA disclosures prompted completion of a proforma identifying ongoing risk/<3/12 (=current DA) with clear management pathway. Patients disclosing current DA were seen by Sexual Health Information Protection (SHIP) team for detailed risk assessment and referrals, as needed. Those with previous DA were offered information/referrals if indicated. Aim(s)/objectives: To review DA disclosure management following DA routine prompt introduction. Methods: A retrospective case-notes review of patients' notes (coded DA) for 3 months from 14/07/2015. Results: 137 patients (111 women, 26 men): age-range 17–75 years old(mean 33), 7% (10/137) commercial sex workers, 11% (15/137) MSM/bisexual. 72% of patients had never disclosed to professionals previously. Ex-regular and current partners most common perpetrators (62%, 15% respectively). 25% (34/137) disclosed current DA. Of these, 94% (32/34) were offered SHIP referral, 88% (28/32) accepted, 75% (21/28) were seen. Referrals were made to DA services 48% (10/21), refuges 10% (2/21), MARAC 19% (4/21). 52% (11/21) had a standardised risk assessment; those who did not, 60% (6/10) were already engaged in services, 20% (2/10) didn't attend follow-up and 20% (2/10) referred to psychology. 44% (14/34) patients were discussed at Vulnerable Adults MDT. No escalation of violence was recorded. Discussion/conclusion: Patients with significant risk from DA were identified who may not have disclosed without routine prompt. This is suggested as the majority were first disclosures. Interventions to reduce the negative consequences of DA for these patients have been performed.